From the Indian Ocean to the Mediterranean: the global trade networks of Armenian merchants from New Julfa - Aslanian, Sebouh David (The California world history library, 2011)
From trade diasporas to circulation society -- Old Julfa, the great deportations, and the founding of New Julfa, 1604/1620 -- The new Julfan trade network I: the world of the Indian Ocean -- The New Julfan trade network II: the Mediterranean, Western European, and Russian Networks -- "The salt in a merchant's letter": the art of writing business correspondence, the courier system, and their role in Julfan economy and society -- Social capital, "trust" and the role of networks in Julfan trade: informal and semi-formal institutions at work -- The circulation of men and credit: the role of the commenda, the family firm and of non-circulating women in Julfan society -- From coalition to nation: the collapse and transformation of the Julfan trade network